Conducting psychological assessment : a guide for practitioners - Wright, A. Jordan (Wiley, 2020)
"It has been about ten years since the original edition of Conducting Psychological Assessment came out, and since then it has been used consistently, especially within educational contexts, to train psychologists in the process of psychological assessment, especially related to integrating data and writing reports. The hypothesis testing model proposed in the original book has become the standard for ethical and rigorous comprehensive (multi-method) assessment. The second edition will take the foundational models from the first edition and add nuance and details that have been hammered out over the past ten years of running CE workshops based on the ideas in the book. Specifically, the author has developed well-received models of reconciling conflicting data from different sources, which can be incorporated into the data integration process chapter. Further, the author has begun to use several other models of personality functioning as a template for conceptualizing data (including the interpersonal circumplex model), which is used illustratively throughout the text"--